SISTEM UBIQUITIN-PROTEASOM DAN HUBUNGANNYA DENGAN KARSINOGENESIS YANG DIINDUKSI OLEH PAPILLOMAVIRUS MANUSIA - Khie Khiong (Fakultas Farmasi Universitas Pancasila, 2003)
Certain types of human papillomaviruses (HPV) have been etiologically associated with malignant lesion, most notably with cervical cancer. The major oncoproteins of these cancerassociated viruses are encoded by the viral E6 and E7 genes and characterization of these oncoproteins has shown that both E6 and E7 exploit the ubiquitin-proteasome system to degrade the cellular proteins.